The problem of primary infection in endo-periodontal lesions: a systematic review - D. A. Moiseev; I. S. Kopetsky; I. A. Nikolskaya; G. S. Ilyukhin; S. Yu. Gazarov; G. K. Madatyan; V. V. Sevastyanova; A. B. Kurbatina (Эндодонтия Today)
The main ways of interrelation of pulp and periodontal tissues are normally the apical openings of the roots of the teeth and additional root canals. In addition, it is important to remember that the bulk of the tooth is dentin, permeated with the smallest dentine tubules, which can also serve as a road in the «endodont-periodontal» system. A doctor who is faced with endo-periodontal lesion (EPL) faces a difficult task, which consists in competent planning of complex treatment and predicting the patient's condition. And one of the main questions that a clinician needs to answer when planning effective prevention and treatment of EPL is «What is primary? ». This systematic review is devoted to the problem of the primacy of infection in EPL, as the most complex and poorly studied.Aim. To summarize the available data on the features of the etiology, pathogenesis, diagnosis and clinical course of EPL.Materials and methods. 3587 publications were found, presented in international lectronic databases: PubMed, Google Search, Ebsco, Embase, Web of Science, ScienceDirect, SciELO and eLibrary from 2000 to 2023. Based on the selection criteria, 65 publications were selected, which included the results of studying the structure of periodontal tissues and tooth pulp, etiology, pathogenesis, as well as the diagnosis and clinical course of EPL. The methodology of this study meets the requirements for systematic reviews and meta-analyses of «PRISMA».Results. The features of pulpo-periodontal relationships are described, data on the prevalence and classification of EPL are presented. Special attention is paid to the etiology of EPL and possible infectious agents involved in the pathogenesis of EPL. The clinical and diagnostic features of the course of EPL and the main approaches to treatment, depending on the primary infection of tissues, are described.Conclusions. The presented detailed systematic analysis showed that the problem of EPL, which has high relevance and significance, has not been studied enough, which does not allow to effectively diagnose, treat, prevent and predict this pathology.